Շարիա դատարանների արձանագրությունները հալեպահայության կարգավիճակի վերաբերյալ (XVII-XIX դ.) - Մակարյան, Վեներա; Մովսես Խեչո («Նաիրի» հրատ.)
Under the Ottoman rule, Armenian citizens, including the Armenian community of Syria, were part of the Millet System. They enjoyed certain autonomy in their community, and issues of concern were resolved in the Millet courts. In addition to the Millet courts, Syrian Armenians sometimes took their cases to the local Sharia courts not only in mandatory cases but also voluntarily. Many records of Sharia courts in Aleppo, 13 of which are kept in Matenadran, refer to this fact. The documents contain information about the Christian citizens of the Ottoman Empire, particularly the status of Armenians in Aleppo, and touch upon issues such as community life, inter-communal relations, religious discrimination, conflicts and their resolution. Под османским владычеством все армяне, в том числе армянская община Сирии, являлись частью Армянского миллета и пользовались определенной автономией в общественной жизни. Вопросы армянской общины решались в судебном порядке Армянского миллета. Однако зафиксированы случаи, когда армяне Сирии, помимо судов миллета, обращались также к местным шариатским судам не только в обязательных случаях, установленных властями, но и добровольно. Об этом свидетельствуют документы шариатских судов Алеппо, 13 из которых хранятся в Матенадаране.
Keywords: Մատենադարանի հավաքածու; Հալեպ; Հայ գաղթօջախներ